Public Perception of Covid-19: Implementation of Health Protocols in West Muna District - Apriani, Apriani; Prasetya, Fikki; Yunawati, Irma (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2021)
Coronavirus Disease (Covid-19) is a group of viruses that can cause disease in humans. Several types of Coronavirus are known to cause respiratory tract infections in humans ranging from coughs to clods and even more severe ones such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). The purpose of this study was to determine the relationship between public perceptions about the safety of wearing masks, keeping a distance, and washing hands on the prevention of Covid-19 transmission in the people of Watumela Village, Lawa District, West Muna Regency. The research method used in this study is an observational cross sectional study using the chi square test. The results showed that people’s perception about the safety of wearing masks (sig = 0.000 <0.05), keeping a distance (sig = 0.000 <0.05), washing hands (sig = 0.000 <0.05) towards preventing Covid-19 transmission. The conclusion of this study is that there is a significant relationship between people’s perceptions about the safety of wearing masks, keeping a distance, and washing hands on the prevention of Covid-19 transmission